Toxoplasmosis in cattle for human consumption in Lima, Peru - Serrano-Martínez, Enrique (2022)
The objective of the study was to evaluate the presence of infection antibodies against Toxoplasma gondii in bovines intended for human consumption, taking into consideration the variables as factors associated with Toxoplasmosis: age group (2 to 3 years, more than 3 to 4 years and over 4 years), sex (female and male), breed (Holstein, Brown Swiss and Mestizo/Criollo) and origin (slaughterhouses located in the North, South, West and East of Lima). For this, blood was extracted from 385 bovines destined for human consumption, which were in 4 official slaughterhouses in Lima, Peru, the blood samples were analyzed using the Indirect Immunofluorescence technique (IFAT), considering animals with antibody titers as positive. equal to or greater than said 1:100 dilution. In addition, the 1:100 antibody titer was made in the positive sera. The results showed that 32.2 ± 4.7% (124/385) of cattle had a positive reaction to the presence of antibodies against T. gondii, no significant statistical difference was found between the variables. The titration of bovine antibodies showed animals with a positive reaction in the dilution of 1/100 (79/124), 1/200 (22/124),1/400 (13/124), 1:800 (6/124), 1:1600 (3/124) and 1:3200 (1/124) by IFAT. The present study evidences the presence of bovines intended for human consumption, seroreactors for T. gondii, a parasite whose form of transmission is the consumption of raw or undercooked meat, whether it comes from bovines or another species. Therefore, it is necessary to highlight the importance of the finding made, in order to develop sanitary measures aimed at ensuring the safety of food products and/or minimizing the possible risks that the consumption of these meat products may mean.